Language Learning Strategy in Writing Process Among English Department Students - Ukhti Sirli Rosa; Erma Rahayu Lestari (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to find out what writing strategies are most widely used in English major classes. This research uses a quantitative approach carried out using a survey method. This research was conducted at Universitas PGRI Jombang by selecting the English classes of fourth semester with a total sample of 58. The respondents were examined through the Language Learning Strategy Questionnaire (LLSQ) as the measurement instrument to check the learning strategy preference. The research results obtained were then calculated using Microsoft Excel and interpreted in quantitative descriptive form. The research results show that the writing method or strategy most often used by students in English classes is the planning method. This is obtained from the mean test on planning which produces a value of 3.57, which is greater than drafting which produces a mean value of 3.51. The most frequently used by the respondents’ is a metacognitive strategy with a mean value of 3.61. Whereas, the least frequently used by the respondents is the social strategy with a mean value of 3.53